Determination of the variability of sugars in date fruit varieties - Zhang, Chuan-Rui; Aldosari, Saleh A.; Vidyasagar, Polana S.P.V.; Shukla, Paraj; Nair, Muraleedharan G. (Journal of Plantation Crops, 2015)
The consumption of date fruit has increased around the world. To meet the demand, numerous varieties of date palms are under commercial production. In this study, total sugars in 29 varieties of date fruits produced in Saudi Arabia were quantified and characterized. The quantification of sugars was done by HPLC using a carbohydrate column and RI detector. Structures of sugars were characterized by NMR methods. Total sugar content in 29 varieties of the dried date fruits ranged from 61.7 to 78.6 per cent. Among these, only Deglet Noor, Sukkari Al Qassim and Nabtat Ali dates contained sucrose. The rest of the varieties showed higher levels of fructose than glucose and were devoid of sucrose. The fructose and glucose existed as a mixture of β-D-fructopyranose and β-D-fructofuranose; and α-D-glucopyranose and β-D-glucopyranose, respectively. Date fruits contain only fructose, glucose and sucrose as carbohydrates. All date fruits in this study, except Sukkari Al Qassim and Deglet Noor, showed higher levels of fructose than other sugars, which support the health benefits of date fruits as dietary components.